A SYSTEMATIC LITERATURE REVIEW: STRATEGI PENGEMBANGAN USAHA MIKRO DAN MENENGAH (UMKM) MELALUI PENINGKATAN KUALITAS SUMBER DAYA MANUSIA - Irhash Abdul Hakam; Krisna Fatahillah; Rini Nur Faniati; Nihayah Nurul Izzah; Riyan Sisiawan Putra (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2023)
Micro, Small and Medium Enterprises (MSMEs) have an important role in Indonesia's economic growth. However, behind the contribution of SMEs Indonesia's economic growth still faces many challenges SMEs face challenges in their internal or external development. Therefore, the MSME development strategy is important for the better development of UKM. So far, the problem that often occurs in SMEs is the low quality of human resources. SMEs experience this Flowering Series. The purpose of this study is to determine the development strategy of micro and medium enterprises (MSMEs) through improving the quality of human resources. The method used in this research is Systematic Literature Review. All articles used for reference in this journal are sourced from Google Scholar, with a publication time of the last 6 years (2018-2023). Based on the results of this study, it aims to carry out a systematic review of existing literature to identify effective strategies in developing MSMEs through improving the quality of human resources. By combining and analyzing findings from previous studies, this research will provide a deeper understanding of strategies that can be implemented to improve the quality of human resources in an effort to strengthen MSMEs.